Ultrasonographic measurement of optic nerve sheath diameter during laparoscopic surgeries in pediatric patients: An observational study - Swarup Ray; Uditi Parmar; Raylene Dias; Vishal Saxen; Fatema Mujpurwala; K A Anu (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Laparoscopic surgery involves creation of carbondioxide (CO2) pneumoperitoneum leading to a rise in intracranial pressure (ICP), which can cause expansion of optic nerve sheath diameter(ONSD).We aimed to study the magnitude of changes in ONSD occurring during pediatric laparoscopic surgery and correlate them with changes in end-tidal CO2 (EtCO2), intrabdominal pressure (IAP), and a change in patient position (P). Material and Methods: Thirty-five pediatric patients between 1 and 12 years undergoing laparoscopic surgeries under general anesthesia were included.The ONSD, EtCO2, IAP, and position (P) in degrees from supine were recorded 15 min post-anesthesia induction(T1) and 30 min following the establishment of pneumoperitoneum (T2).The difference between the two groups was analyzed using a paired or unpaired t-test for quantitative variables and using Chi-square or Fisher’s exact test for qualitative data.Correlation between two quantitative variables was performed using Pearson’s correlation coefficient. Results: Mean ONSD showed a significant change (P < 0.001) 30 min (T2) following pneumoperitoneum increasing by an average of 0.04cm as compared to 15 min (T1) post-anesthesia induction (0.57 ± 0.06 vs. 0.61 ± 0.06). There was a moderate to strong positive correlation between change in ONSD and change in EtCO2(correlation coefficient = 0.629, P = 0.001) 30 min post pneumoperitoneum. There was a weak correlation between change in ONSD and change in position (correlation coefficient = 0.276) and a very weak correlation between change in ONSD and change in IAP (correlation coefficient = 0.19). Conclusions: Laparoscopic surgeries in children can cause significant increases in ICP as measured by the ONSD; changes in EtCO2 are the predominant factor responsible. Increasing minute ventilation to maintain normal EtCO2 may help mitigate changes in ICP in children undergoing laparoscopic surgery.